Swine flu H1N1 the facts - Stephenson, Terence (London Philadelphia Jessica Kingsley, 2009)
Presents an introduction to the swine influenza in the United States, discussing its symptoms, treatment, preventive measures that can be taken, impact of the virus on children, and information about the vaccination and its effectiveness
Also published under the title: Swine flu : what parents need to know
Includes bibliographical references (p. 156) and index
1 13
Keywords: H1N1 influenza; Influenza; Influenza A Virus, H1N1 Subtype -- Popular Works; Influenza, Human -- Popular Works